The Impact of Financial Literacy, Financial Socialization Agents, and Parental Norm on Money Management of Universitas Tarumanagara Students - Steffani Nugraha; Herlina Budiono; Hendra Wiyanto (Graduate Program of Universitas Tarumanagara, 2023)
The aim of this research is to determine the impact of financial literacy, financial socialization agents, and parental norm on money management of Universitas Tarumanagara students. This study used 163 respondents from the students of the Faculty of Economics and Business, Universitas Tarumanagara. Data collected in this study using a questionnaire. The research design in this study used descriptive research with the sampling technique used non-probability sampling technique, namely convenience sampling. Analysis of the data used is the Structural Equation Model (SEM) using the Smart-PLS version 3.3.5 software as a data analysis tool. The results obtained in this study are financial literacy has a positive and significant impact on money management of Universitas Tarumanagara students, financial socialization agents have a positive and significant impact on money management of Universitas Tarumanagara students, and parental norm has a positive and significant impact on the money management of Universitas Tarumanagara students.